1980
DOI: 10.1017/s0016756800033070
|View full text |Cite
|
Sign up to set email alerts
|

On polygenetic myrmekite

Abstract: A brief review of Becke's (1908) replacement and Schwantke's (1909) exsolution models for myrmekite genesis and further consideration of the morphology and spatial distribution of myrmekite as outlined by Phillips (1974) lead to the conclusion that both hypotheses have a place in explaining the origin of myrmekite. The Schwantke model is generally best applied, for example, to high-level undeformed massive granitoids and the Becke model to deformed metamorphic rocks. The latter hypothesis and a third model inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

1989
1989
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(24 citation statements)
references
References 18 publications
0
21
0
3
Order By: Relevance
“…The two main hypotheses for myrmekite development are those of replacement reactions (Becke, 1908) and solid-state exsolution (Schwantke, 1909). These ideas and variations thereon have been summarized and discussed in &tail by Sturt (1970), Widenfalk (1972), Smith (1974) and Phillips (1974;1980). In Schwantke's lattice diffusion model, a change in solid composition m u m in response to elastic strain gradients, but requires a relatively long time to accomplish (see also Bayly, 1987).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The two main hypotheses for myrmekite development are those of replacement reactions (Becke, 1908) and solid-state exsolution (Schwantke, 1909). These ideas and variations thereon have been summarized and discussed in &tail by Sturt (1970), Widenfalk (1972), Smith (1974) and Phillips (1974;1980). In Schwantke's lattice diffusion model, a change in solid composition m u m in response to elastic strain gradients, but requires a relatively long time to accomplish (see also Bayly, 1987).…”
Section: Discussionmentioning
confidence: 99%
“…5a very well, when the reaction proceeds to the right. The Phillips (1980) modification of the Becke model requires the introduction of H,O into the reactions, so that muscovite forms at the expense of the existing K-feldspar . and plagioclase, and K,O is removed from the local environment.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, muscovite is expected to form together with myrmekite in a closed system, without implying the occurrence of K-metasomatism suggested by Phillips (1980).…”
Section: Metamorphic Myrmekite Coronasmentioning
confidence: 95%
“…For Phillips (1974Phillips ( , 1980, and Smith & Brown (1988), the myrmekite is formed by the exsolution of alkali feldspar accompanied of pressure-induced dissolution and reprecipitation in a subsolidus state with some participation of primary quartz and K-feldspar. Smith & Brown (1988) suggested that subsequent processes could partially or completely modify the myrmekite by recrystallizing it.…”
Section: Texture and Deformation Of Terra Preta And Canoas Granitoidsmentioning
confidence: 99%